2018
DOI: 10.18203/2394-6040.ijcmph20184811
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors that motivate and prevent the blood donation decision among the medical college students

Abstract: Background: Human blood is an essential element of human life. Medical colleges students can be very good source for voluntary blood donation. This study was done with the objectives - to find out the factors motivating blood donation and the factors responsible for not donating the blood among the medical students.Methods: A cross sectional study was conducted among the students of a government autonomous medical college, situated at northern part of Karnataka, India. Data was collected by a pre tested, semi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…[22][23][24] In this study being a third year of study was a positive significant predictor which was comparable with studies done in Ambo University and Addis Ababa University, Ethiopia, Kenya and India in which the university students' increased year of study has a significant association with blood donation practice. 17,19,25,26 This study also showed that blood donation is different by sex. Female students were more likely to donate blood than males, which is consistent with studies done among Namibia University, 21 Nigeria, Hong Kong and Spain University which showed that females have more potential of being voluntary donors than males.…”
Section: Discussionmentioning
confidence: 51%
“…[22][23][24] In this study being a third year of study was a positive significant predictor which was comparable with studies done in Ambo University and Addis Ababa University, Ethiopia, Kenya and India in which the university students' increased year of study has a significant association with blood donation practice. 17,19,25,26 This study also showed that blood donation is different by sex. Female students were more likely to donate blood than males, which is consistent with studies done among Namibia University, 21 Nigeria, Hong Kong and Spain University which showed that females have more potential of being voluntary donors than males.…”
Section: Discussionmentioning
confidence: 51%